Detection of the "small for gestational age" fetus: comparison of a teaching hospital with field clinics - Senanayake, H; Bujawansa, S; Premaratna, E D (The Sri Lanka Medical Association, 2003)
INTRODUCTION: Low birthweight babies make a disproportionate contribution to perinatal morbidity and mortality. Antenatally they manifest as "small for gestational age" fetuses. Their detection is an important aspect of antenatal care. OBJECTIVES: To compare the effectiveness of antenatal detection of "small for gestational age", fetuses by a clinic in a teaching hospital and field clinics. DESIGN: Comparative descriptive study. SETTING: Professorial Obstetric Unit of De Soysa Maternity Hospital, Colombo. METHODS: Antenatal records of 67 consecutive women who delivered low birthweight babies at term were reviewed. Entries in the teaching hospital clinic records and the pregnancy record of the field clinics were studied. A deviation corresponding to more than two weeks' growth was considered significant. The period of gestation at which the deviation was first detected and any follow up action taken were noted. RESULTS: Of the total sample of 67 women 56 had also attended a field clinic. A significantly greater percentage of small for dates fetuses were detected by the primary care staff (71.4 vs 53.7%; p < 0.05). They also detected them earlier in pregnancy (26.4 vs 30.7 weeks; p < 0.05). However, referral for specialised care was arranged only in 32% by the field clinics. CONCLUSION: The detection rate of small for gestational age fetuses by staff of field clinics was close to the higher rates quoted in the literature. Only a minority of these fetuses were assessed further in both settings indicating a deficiency in antenatal care.